Challenges in recruiting frequent users of ambulance services for a community paramedic home visit program - Mikayla Plishka; Ricardo Angeles; Melissa Pirrie; Francine Marzanek; Gina Agarwal (BMC, 2023)
Abstract Background The Community Paramedicine at Home (CP@home) program is a health promotion program where community paramedics conduct risk assessments with frequent 9-1-1 callers in their homes, with a goal of reducing the frequency of 9-1-1 calls in this vulnerable population. The effectiveness of the CP@home program was investigated through a community-based RCT conducted in four regions in Ontario, Canada. The purpose of this current recruitment study is to examine the challenges met when recruiting for a community randomized control trial on high frequency 9-1-1 callers. Methods Eligible participants were recruited from one of four regions participating in the CP@home program and were randomly assigned to an intervention group (n = 1142) or control group (n = 1142). Data were collected during the recruitment process from the administrative database of the four paramedic services. Whether they live alone, their parental ethnicity, age, reason for calling 9-1-1, reason for not participating, contact method, and whether they were successfully contacted were recorded. Statistical significance was calculated using the Chi-Squared Test and Fisher's Exact Test to evaluate the effectiveness of the recruitment methods used to enroll eligible participants in the CP@home Program. Results Of the people who were contacted, 48.0% answered their phone when called and 53.9% answered their door when a home visit was attempted. In Total, 110 (33.1%) of people where a contact attempt was successful participated in the CP@home program. Most participants were over the age of 65, even though people as young as 18 were contacted. Older adults who called 9-1-1 for a lift assist were more likely to participate, compared to any other individual reason recorded, and were most often recruited through a home visit. Conclusions This recruitment analysis successfully describes the challenges experienced by researchers when recruiting frequent 9-1-1 callers, which are considered a hard-to-reach population. The differences in age, contact method, and reason for calling 9-1-1 amongst people contacted and participants should be considered when recruiting this population for future research.